2015
DOI: 10.1371/journal.pone.0132062
|View full text |Cite
|
Sign up to set email alerts
|

Salix purpurea Stimulates the Expression of Specific Bacterial Xenobiotic Degradation Genes in a Soil Contaminated with Hydrocarbons

Abstract: The objectives of this study were to uncover Salix purpurea-microbe xenobiotic degradation systems that could be harnessed in rhizoremediation, and to identify microorganisms that are likely involved in these partnerships. To do so, we tested S. purpurea‘s ability to stimulate the expression of 10 marker microbial oxygenase genes in a soil contaminated with hydrocarbons. In what appeared to be a detoxification rhizosphere effect, transcripts encoding for alkane 1-monooxygenases, cytochrome P450 monooxygenases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 85 publications
1
44
0
1
Order By: Relevance
“…This genus comprises known plant symbionts and nitrogen-fixing bacteria, and more recently some have been reported as capable to degrade PAHs4647. Furthermore, genomic analysis showed that some species of Rhizobium , Bradyrhizobium and Mesorhizobium additionally harbour multiple genes for acyl-homoserine lactone (AHL) or autoinducer (AI) quorum-sensing (QS) molecules, which may suggest that bacterial hydrocarbon degradation is a QS-regulated process4648.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This genus comprises known plant symbionts and nitrogen-fixing bacteria, and more recently some have been reported as capable to degrade PAHs4647. Furthermore, genomic analysis showed that some species of Rhizobium , Bradyrhizobium and Mesorhizobium additionally harbour multiple genes for acyl-homoserine lactone (AHL) or autoinducer (AI) quorum-sensing (QS) molecules, which may suggest that bacterial hydrocarbon degradation is a QS-regulated process4648.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, genomic analysis showed that some species of Rhizobium , Bradyrhizobium and Mesorhizobium additionally harbour multiple genes for acyl-homoserine lactone (AHL) or autoinducer (AI) quorum-sensing (QS) molecules, which may suggest that bacterial hydrocarbon degradation is a QS-regulated process4648. Several studies have demonstrated that degradation of environmental contaminants is enhanced in the plant rhizosphere4749 and inoculation with Rhizobium melitoti was reported to specifically stimulate the growth and activity of indigenous hydrocarbon-degrading microorganisms50. In the light of these observations, our data further support the concept that increased selection pressure due to exposure to contaminants stimulates communication and cooperation amongst members of the permafrost microbial community, especially in the upper active layer.…”
Section: Discussionmentioning
confidence: 99%
“…Similar reason could also be deduced for other legumes species in which only 2.77 and 6.46% concentration of the fraction was recovered from the residual oil extracted from A. hypogea and M. sativa, respectively. This is not surprising as many authors reported that the enhancement of specific organisms may lead to the preferential degradation of either aliphatics or aromatics, with degradation of the remaining class of compounds being inhibited as a result of catabolite repression (Rentz et al 2004;Phillips 2008;Martin et al 2014;Pagé et al 2015).…”
Section: Dissipation Of Petroleum Hydrocarbons In the Rhizospherementioning
confidence: 96%
“…For instance, in a pot study, transcripts related to Alphaproteobacteria , Betaproteobacteria , Gammaproteobacteria and Acidobacteria were more abundant in the rhizosphere of willows growing in contaminated soil as compared to non‐contaminated soils (Yergeau et al ., ). Also, functional genes related to aromatic and aliphatic hydrocarbon degradation were more prevalent in the rhizosphere of willows growing in contaminated soils (Yergeau et al ., ), and these genes were shown to be related to bacterial orders such as Actinomycetales , Rhodospirillales , Burkholderiales , Alteromonadales , Solirubrobacterales , Caulobacterales and Rhizobiales (Pagé et al ., ). In the field, the differences in the expression of hydrocarbon degradation genes and in the active taxa between the rhizosphere of willows growing in contaminated and non‐con‐taminated soils varied and depended on the willow species (Yergeau et al ., ).…”
Section: Soil Organismsmentioning
confidence: 97%
“…Generally, indigenous hydrocarbon‐degrading microbes in contaminated soils can be efficiently stimulated by plants (Yergeau et al ., ; Pagé et al ., ) or fertilizers (Yergeau et al ., , ; Bell et al ., ). Bioaugmentation (inoculations) with a single or a few hydrocarbon‐degrading strains is thus generally ineffective (Thomassin‐Lacroix et al ., ), and it has been shown that pre‐selecting microorganisms that can degrade hydrocarbons results in less efficient degradation than using the entirety of the microbes present in a soil (Bell et al ., ).…”
Section: Rhizoremediation As a Model For Microbiome Manipulationmentioning
confidence: 99%